PENERAPAN MEDIA POP-UP BOOK UNTUK PEMAHAMAN SUB TEMA KETAMPAKAN RUPA BUMI DI SEKOLAH DASAR - Safrina Junita; Munzir (Jurnal Tunas Bangsa, 2020)
This research is motivated by the results of observations and interviews conducted by researchers in several elementary schools in Aceh Besar and Banda Aceh which explain that teachers are still having trouble finding suitable media for learning, especially on themes that contain a lot of reading, one of them is in grade III elementary school , as in the sub-theme of the appearance of the earth with the characteristics of the sub-theme in the form of abstract material concepts and understanding is obtained by reading a lot so that an innovation is needed so that students remain active and can increase students' understanding during learning. The purpose of this research is to apply pop-up book learning media for students' understanding of the sub-theme of the appearance of the earth. The results of the application of the pop-up book media on the sub-theme of appearance of the earth can improve the understanding of students in class III SD 69 of the sub-theme. This is evidenced by the acquisition of student learning outcomes in the posttest with a percentage of 86.2% of students included in the category "Completed". Whereas in the pretest no students were declared "Complete". The results of student motivation to pop-up book media were very high at 87.6% and students stated that they were motivated by using pop-up book learning media. Abstrak Penelitian ini dilatar belakangi oleh hasil observasi dan wawancara yang peneliti lakukan di beberapa sekolah dasar di Aceh Besar dan Banda Aceh yang menjelaskanbahwa guru masih kesulitan menemukan media yang cocok untuk pembelajaran terutama pada tema-tema yang mengandung banyak bacaan salah satunya adalah di kelas III SD,seperti pada sub tema ketampakan rupa bumi dengan karekteristik sub tema tersebut berupa konsep materi yang bersifat abstrak dan pemahamanannya didapat dengan banyak membaca sehingga dibutuhkan suatu inovasi supaya peserta didik tetap aktif dan dapat meningkatkan pemahaman peserta didik selama pembelajaran. Tujuan penelitian ini adalah menerapkan media pembelajaran pop-up bookuntuk pemahaman siswa terhadap sub tema ketampakan rupa bumi. Hasil penerapan media pop-up book pada sub tema ketampakan rupa bumi dapat meningkatkan pemahaman siswa kelas III SD 69 terhadap sub tema tersebut. Hal ini dibuktikan dengan perolehan nilai hasil belajar siswa pada posttest dengan persentase 86,2% siswa termasuk dalam katagori ”Tuntas” . Sedangkan pada pretest tidak ada siswa yang dinyatakan “Tuntas”. Hasil motivasi belajar siswa terhadap media pop-up book sangat tinggi yaitu 87,6% dan siswa menyatakan termotivasi dengan penggunaan media pembelajaran pop-up book. Kata Kunci: Media Pembelajaran, Ketampakan Rupa Bumi, Pop-Up Book